Clinical Characteristics and Early Interventional Responses in Patients with Severe COVID-19 Pneumonia. (2nd June 2021) - He, Susu; Fang, Lina; Xia, Lingzhen; Lin, Shuangxiang; Ye, Junhui; Luo, Dinghai
Abstract : Progressive acute respiratory distress syndrome (ARDS) is the most lethal cause in patients with severe COVID-19 pneumonia due to uncontrolled inflammatory reaction, for which we found that early intervention of combined treatment with methylprednisolone and human immunoglobulin is a highly effective therapy to improve the prognosis of COVID-19-induced pneumonia patients. Objective . Herein, we have demonstrated the clinical manifestations, laboratory, and radiological characteristics of patients with severe Coronavirus Disease-2019 (COVID-19) pneumonia, as well as measures to ensure early diagnosis and intervention for improving clinical outcomes of COVID-19 patients. Summary Background Data . The COVID-19 is a new infection caused by a severe acute respiratory syndrome- (SARS-) like coronavirus that emerged in China in December 2019 and has claimed millions of lives. Methods . We included 37 severe COVID-19 pneumonia patients who were hospitalized at Taizhou Public Health Medical Center in Zhejiang province from January 17, 2020, to February 18, 2020. Demographic, clinical, and laboratory features; imaging characteristics; treatment history; and clinical outcomes of all patients were collected from electronic medical records. Results . The patients' mean age was 54 years (interquartile range, 43−64), with a slightly higher male preponderance (57%). The most common clinical features of COVID-19 pneumonia were fever (29 (78%)), dry cough (28 (76%)), dyspnea (9 (24%)), and fatigue (9 (24%)). Serum interleukin (IL)-6 and IL-10 were elevated in 35 (95%) and 19 (51%) patients, respectively. Chest computerized tomography scan revealed bilateral pneumonia in 35 (95%) patients. Early intervention with a combination of methylprednisolone and human immunoglobulin was highly effective in improving the prognosis of these patients. Conclusions . Progressive acute respiratory distress syndrome is the most common cause of death in patients with severe COVID-19 pneumonia owing to an uncontrolled inflammatory response. Early intervention with methylprednisolone and human immunoglobulin was highly effective in improving their prognosis.